Brachytherapy in the treatment of skin cancer: an overview - Skowronek, Janusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
The incidence of skin cancer worldwide is constantly growing and it is the most frequently diagnosed tumor. Brachytherapy (BT) in particular localizations is a valuable tool of the exact radiation depot inside the tumor mass. In localizations such as the face, skull skin and inoperable tumors, relapses after surgery, radiotherapy are usually not suitable for primary or secondary invasive treatment. Brachytherapy is a safe procedure for organs at risk according to rapid fall of a dose outside the axis of the applicator with satisfactory dose localization inside the target. The complications rate is acceptable and treatment costs are low. In some tumors (great skin lesions in the scalp, near eyes or on the nose) BT allows for a great dose reduction in surrounding healthy tissues. Brachytherapy provides minimal dose delivery to surrounding healthy tissue, thus enabling good functional and cosmetic results. Treatment is possible almost in all cases on an outpatient basis.